Análisis de factibilidad para la implementación de la tecnología móvil 5g en la ciudad de Babahoyo - Cavero Valero, Maria Elisa (2019)
This case study is based on the feasibility analysis for the implementation of 5G mobile technology in the city of Babahoyo, on the basis that this network is still under development and very satisfactory tests of its use, scope and Its good implementation in Ecuador already speaks at the government level about this technology and already has policies to turn the country into a digital state. It will also detail what the new 5G technology implies, its advantages and disadvantages, as well as the characteristics of the technologies prior to it and its operation, thus deducing that the new 5G technology has the fastest data transport speed. The main objective is to improve the speed of data transmission in telephone networks by analyzing the existing infrastructure, and the technological services provided by mobile operators within the city of Babahoyo and thus be able to implement a network that satisfies the user. In this case, for the verification of the feasibility of the project, the quantitative and observation method was used, where a certain number of residents of the city were found where the need and difficulty of implementing 5G mobile technology can be considered and just as it was also possible to observe and discover directly how the processes of the new technology are being carried out. Finally, a scheme was developed in which the SDN and small cell architecture is used, in order to distribute the mobile service to the devices connected through the base radio, in addition the main elements and costs that the implementation of the implementation of the 5G mobile technology